2021
DOI: 10.1007/978-3-030-85397-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mesoporous Silica Nanoparticles as Drug Carriers: Evaluation of Diverse Mesoporous Material Nanoparticles as Potential Host for Various Applications

Abstract: Effective treatment of patients suffering from fatal diseases such as cancer, AIDS, tuberculosis, etc., has always been a challenge, and new approaches are continuously explored so as to prevent or reduce the toxic side effects of such drugs. The exploration of silica-based mesoporous nanoparticles as a host for better therapeutic action of drugs has provided some very positive and encouraging outcomes. The characteristics of these mesoporous materials needed for maximum loading of the drug and then the subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Though there has been an early in-human study which showed silica gel was equivalent to acyclovir in the topical treatment for herpes labialis ( Zschocke et al, 2008 ), similar subsequent in-human studies have not been attempted and development in this area had remained slow before the COVID-19 pandemic. However, with the widespread use of the latest LNP based mRNA vaccines against SARS-CoV-2, interest in silica-based nanoparticle vaccines has been invigorated ( Rajput et al, 2022 ).…”
Section: Current Limitations and Future Directionsmentioning
confidence: 99%
“…Though there has been an early in-human study which showed silica gel was equivalent to acyclovir in the topical treatment for herpes labialis ( Zschocke et al, 2008 ), similar subsequent in-human studies have not been attempted and development in this area had remained slow before the COVID-19 pandemic. However, with the widespread use of the latest LNP based mRNA vaccines against SARS-CoV-2, interest in silica-based nanoparticle vaccines has been invigorated ( Rajput et al, 2022 ).…”
Section: Current Limitations and Future Directionsmentioning
confidence: 99%